Association of On-Post and Off-Post Resources With Perception of Residential Neighborhood Quality in U.S. Army Families. (3rd July 2018) - Mash, Holly B. Herberman; Fullerton, Carol S.; Cozza, Stephen J.; McCarroll, James E.; Ursano, Robert J.
ABSTRACT: This study examined the relationship of on- and off-post resources to perceived residential neighborhood quality in 432 soldiers and their spouses from the four largest U.S. Army installations. Participants completed a questionnaire that measured one important element of perceived neighborhood quality (social cohesion/interrelatedness) and the extent to which community resources met the needs of military families. Higher levels of perceived on- and off-post resources were independently related to greater perceived neighborhood quality. After adjusting for demographics and off-post resources, on-post resources continued to be associated with perceived neighborhood quality ( B = .17, p ≤ .01). Access to diverse, high-quality, and readily available community resources, particularly on-post, may enhance perceived neighborhood quality and strengthen military communities.